Maternal and fetal outcomes in cases of accidental haemorrhage at a tertiary care centre: a prospective observational study - Desai, Karan; Damor, Mittal; Hirpara, Pinal; Patel , Akansha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Accidental haemorrhage is a major obstetric emergency associated with significant maternal and perinatal morbidity and mortality. Early recognition and timely management are crucial to improve outcomes, especially in resource-limited settings where anemia and hypertensive disorders are common. Methods: A prospective observational study was conducted in the Department of Obstetrics and Gynaecology at NHL Municipal Medical College Ahmedabad Gujarat a tertiary care teaching hospital from December 2022 to March 2025. All pregnant women ≥28 weeks’ gestation diagnosed with accidental haemorrhage were included. Women with bleeding due to other causes or <28 week’s gestation were excluded. Maternal demographics, risk factors, clinical features, management, and maternal and fetal outcomes were analysed. The collected data were compiled and analysed using Microsoft Excel 2019 (Microsoft Corporation, USA). Descriptive statistics were applied, and the results were expressed as frequencies and percentages. Results: Among 11,560 deliveries, 105 cases of accidental haemorrhage were recorded (incidence 0.90%). Most women were unbooked (64.76%) and from lower socio-economic class (67.62%). Common risk factors were anemia (61.90%) and hypertensive disorders (47.61%). Abdominal pain (71.42%) and vaginal bleeding (61.90%) were the main symptoms. Cesarean section was performed in 56.20% cases. Blood transfusion was required in 66.66%. Major maternal complications included anemia (66.66%), shock (31.42%), PPH (22.85%), and DIC (7.61%), with no maternal mortality. Live birth rate was 63.80%, while perinatal mortality was 44.75%, largely due to prematurity and asphyxia. Conclusions: Accidental haemorrhage remains a serious contributor to adverse fetomaternal outcomes. Strengthening antenatal care, early detection of anemia and hypertension, timely referral, and availability of comprehensive emergency obstetric care can substantially reduce morbidity and mortality.